PRAKTIK WACANA NYESEK BAGI PEREMPUAN SASAK - Devi Adlina Putri; Sri Kusumo Habsari; Susanto Susanto (Kafa`ah: Journal of Gender Studies, 2020)
Benchmarks for ideality for the body that prioritize aspects of physical appearance as well as social demands of the Sasak people who determine women should be able to nyesek or make sesek cloth as a source of value and meaning to the body. This article aims to examine the centrality of the body to explain how the discourse of nyesek is used as a benchmark of female maturity and as a standardization of the ideal wife in the Sasak tribe. This research tries to identify various traditional discourses in the Sasak tribe and study how these discourses function to discipline women. This study also tries to see the views of Sasak women, both the older generation and the younger generation, about the concept of nyesek. This research applies a qualitative descriptive approach. Data obtained through interviews with Sasak women in the range (18-80s). Since most sesek weavers are elderly who can only use the Sasak language, interpreting it into Indonesian requires an interview with a young Sasak tribe. This research seeks to show that the ability of nyesek to be learned by Sasak women not only serves to preserve tradition, but also to encourage women to have an economic role in the family. That is because most of the respondents interviewed were farmers' wives, nyesek was considered as an additional family income, even though its contribution was still small. This research is important because there are still many Sasak women who are not aware of the existence of body control through the discourse contained in the nyesek tradition.